Melatonin shapes bacterial clearance function of porcine macrophages during enterotoxigenic Escherichia coli infection - Lingfei Du; Bingnan Liu; Ziyi Han; Yaoyao Xia; Miaomiao Wu; Shaojuan Liu (Animal Nutrition, 2022)
Due to the immature gastrointestinal immune system, weaning piglets are highly susceptible to pathogens, e.g., enterotoxigenic Escherichia coli (ETEC). Generally, pathogens activate the immune cells (e.g., macrophages) and shape intracellular metabolism (including amino acid metabolism); nevertheless, the metabolic cues of tryptophan (especially melatonin pathway) in directing porcine macrophage function during ETEC infection remain unclear. Therefore, this study aimed to investigate the changes in the serotonin pathway of porcine macrophages during ETEC infection and the effect of melatonin on porcine macrophage functions. Porcine macrophages (3D4/21 cells) were infected with ETEC, and the change of serotonin pathway was analysed by reverse transcription PCR and metabolomic analysis. The effect of melatonin on porcine macrophage function was also studied with proteomic analysis. In order to investigate the effect of melatonin on bacterial clearance function of porcine macrophages during ETEC infection, methods such as bacterial counting, reverse transcription PCR and western blotting were used to detect the corresponding indicators. The results showed that ETEC infection blocked melatonin production in porcine macrophages (P < 0.05) which is largely associated with the heat-stable enterotoxin b (STb) of ETEC (P < 0.05). Interestingly, melatonin altered porcine macrophage functions, including bacteriostatic and bactericidal activities based on proteomic analysis. In addition, melatonin pre-treatment significantly reduced extracellular lactate dehydrogenase (LDH) activity (P < 0.05), indicating that melatonin also attenuated ETEC-triggered macrophage death. Moreover, melatonin pre-treatment resulted in the decrease of viable ETEC in 3D4/21 cells (P < 0.05), suggesting that melatonin enhances bacterial clearance of porcine macrophages. These results suggest that melatonin is particularly important in shaping porcine macrophage function during ETEC infection.